Infrastructural Semiotics and Infrastructural Citizenship: A Critical Discourse Analysis of Linguistic Stratification and the Hydrosocial Contract in Urban Cameroon (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
This sociolinguistic ethnography introduces and operationalizes the concepts of "infrastructural semiotics" and "infrastructural citizenship" through a Critical Discourse Analysis to examine how power, inequality, and civic belonging are discursively constructed around urban water access in Yaoundé, Cameroon. Through a 12-month multimodal study conducted between January and December 2022, this paper synthesizes political economy and Critical Discourse Analysis within a dialectical-relational framework to dissect the stratified linguistic markets materializing around hydrological infrastructure. The analysis identifies and deconstructs three dominant registers: a French-dominant state-corporate register that deploys technocratic depoliticization, a multilingual grassroots-complaint register that functions as a tactical counter-discourse, and an English-French NGO-developmental register that propagates a neoliberal ethos. Drawing on approximately 150 hours of recorded interactions, 65 semi-structured interviews, a systematic multimodal photographic corpus, and policy documents, the paper demonstrates that discourse is a core infrastructural technology where linguistic competence constitutes symbolic capital, directly mediating one's ability to claim rights. It argues that the struggle for water is fundamentally a struggle over the linguistic and semiotic terms of recognition within a fragmented state, revealing the co-constitutive relationship between material scarcity and communicative injustice in a polity defined by its colonial linguistic legacy and profound diversity of over 280 indigenous languages. The paper concludes that infrastructural citizenship is forged in this contested terrain, with significant implications for understanding the nexus of language, power, and resource justice in multilingual, postcolonial states.
Keywords: infrastructure; semiotics; citizenship; political economy; water access